2010
DOI: 10.1038/ismej.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Dominant and diet-responsive groups of bacteria within the human colonic microbiota

Abstract: The populations of dominant species within the human colonic microbiota can potentially be modified by dietary intake with consequences for health. Here we examined the influence of precisely controlled diets in 14 overweight men. Volunteers were provided successively with a control diet, diets high in resistant starch (RS) or non-starch polysaccharides (NSPs) and a reduced carbohydrate weight loss (WL) diet, over 10 weeks. Analysis of 16S rRNA sequences in stool samples of six volunteers detected 320 phylotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
1,140
11
20

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,427 publications
(1,268 citation statements)
references
References 57 publications
60
1,140
11
20
Order By: Relevance
“…Moreover, R. bromii was suggested to be a keystone species in resistant starch degradation, particularly type 3, which is required for the other bacteria to utilize the products from resistant starch [57]. Concordantly to the other studies [16,55,56], the Ruminococcus genus (including R. bromii ) increased in relative abundance in growing pigs that were fed with a type 3 resistant starch-containing diet [30]. An alteration in gut microbiome and a predominance of beneficial bacterial populations were observed in these pigs compared to control pigs.…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, R. bromii was suggested to be a keystone species in resistant starch degradation, particularly type 3, which is required for the other bacteria to utilize the products from resistant starch [57]. Concordantly to the other studies [16,55,56], the Ruminococcus genus (including R. bromii ) increased in relative abundance in growing pigs that were fed with a type 3 resistant starch-containing diet [30]. An alteration in gut microbiome and a predominance of beneficial bacterial populations were observed in these pigs compared to control pigs.…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 71%
“…bromii , E. rectale and Roseburia spp. populations in the gut of different animal models and humans [16,55,56]. Moreover, R. bromii was suggested to be a keystone species in resistant starch degradation, particularly type 3, which is required for the other bacteria to utilize the products from resistant starch [57].…”
Section: Important Dietary Components For the Gut Microbiotamentioning
confidence: 99%
“…), resistant starch (stimulates bifidobacteria, Bacteroides spp., Ruminococcus bromii, E. rectale and Roseburia spp. ), β-glucan (stimulates bifidobacteria) and fructan (stimulates bifidobacteria, Bacteroides spp., lactobacilli and butyrate-producers) are well recognised (144,(154)(155)(156)(157)(158)(159)(160)(161) . In addition, arabinoxylan-oligosaccharides, which are enzymatic hydrolysis products of arabinoxylan, have been shown to stimulate the growth of bifidobacteria in some studies (156) .…”
Section: Fermentable Dietary Carbohydratesmentioning
confidence: 99%
“…Why are the effects so small? One reason could be that the effect of the diet changes on the microbiota did not overcome the inter‐subject variations in the intestinal microbiota (Walker et al ., 2011; Wu et al ., 2011). Notably, only studies using a cross‐over design where both diets were given to the same subjects showed clear effects (David et al ., 2014).…”
Section: Biome Engineering: Modifying the Nutrient Inputmentioning
confidence: 99%